Cytogenetic damage in circulating lymphocytes and buccal mucosa cells of head-and-neck cancer patients undergoing radiotherapy - Minicucci, E. M.; Kowalski, L. P.; Maia, MAC; Pereira, A.; Ribeiro, Lúcia Regina [UNESP]; de Camargo, JLV; Salvador, DMF (Japan Radiation Research Soc, 2005)
This study evaluated cytogenetic damage by measuring the frequency of micronucleated cells (MNC) in peripheral blood and buccal mucosa of head-and-neck cancer patients undergoing radiotherapy.MNC frequencies were assessed in 31 patients before, during, and after radiotherapy, and in 17 C, healthy controls matched for gender, age, and smoking habits. Results showed no statistically significant difference between patients and controls prior to radiotherapy in cytokinesis-blocked lymphocytes or buccal mucosa cells. During treatment, increased MNC frequencies were observed in both cell types. Micronucleated lymphocyte levels remained high in samples collected 30 to 140 days after the end of treatment, while MNC frequency in buccal mucosa decreased to values statistically similar to baseline values. There is controversy over the effects of age, smoking habit, tumor stage, and/or metastasis on MNC frequency. However, increased frequency of micronucleated buccal mucosa cells was seen in patients under 60 years old and in those with tumors >4cm.In conclusion, the data show that radiotherapy has a potent clastogenic effect in Circulating lymphocytes and buccal mucosa cells of head-and-neck cancer patients, and that the baseline MNC frequency in these two tissues is not a sensitive marker for head-and neck neoplasm.